2013
DOI: 10.2174/1871523011312010004
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine: An Old Wine in a New Bottle?

Abstract: Although colchicine, a natural product, is one of the oldest drugs still currently available, its possible functions seem to be surprisingly not well-known. Beyond its present medicinal use (gout, familial Mediterranean fever, Behcet's disease, chondrocalcinosis and other crystal arthritis), numerous other conditions have been recently proposed for the use of this drug, including pericardial diseases. However, colchicine appears as a double-edged sword, with underestimated toxicity and frequent side effects. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 82 publications
1
58
0
5
Order By: Relevance
“…Colchicine is the mainstay treatment in FMF, and most therapeutic actions are attributed to its effect on microtubule cytoskeleton, interfering with several cellular functions 38 39. Since it accumulates preferentially in PMNs,39 and cytoskeletal machinery is required for NETs formation,32 40 we studied the in vitro effect of colchicine on NET release and IL-1β production.…”
Section: Resultsmentioning
confidence: 99%
“…Colchicine is the mainstay treatment in FMF, and most therapeutic actions are attributed to its effect on microtubule cytoskeleton, interfering with several cellular functions 38 39. Since it accumulates preferentially in PMNs,39 and cytoskeletal machinery is required for NETs formation,32 40 we studied the in vitro effect of colchicine on NET release and IL-1β production.…”
Section: Resultsmentioning
confidence: 99%
“…The microtubule inhibitor colchicine, a natural compound derived from flowering plants of the genus Colchicum and Gloriosa superba (Roubille et al 2013), arrests the cell cycle in eukaryotic cells at mitosis. The effect of colchicine is the result of its binding to tubulin subunits and the subsequent disruption of the microtubule dynamics (Chakraborty et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful spindle poison and could exert anti-inflammatory effects. Whenever has been used at low doses, it can be found in white blood cells interfering with many functions as migration and degranulation, blocking tubulin polymerization, microtubule generation and stability [28]. In conclusion, this study appears to be the first in the literature showing the effect of colchicine on experimental colitis.…”
Section: Discussionmentioning
confidence: 65%
“…However, decreased MPO activity in oral treatment group may be an important finding as the marker of neutrophilic infiltration that colchicine therapy may effect as a systemic anti-inflammatory agent. The anti-inflammatory effects are the decreased IL-1 activation, TNF-alfa and leukotriene levels and decreased inflammasome activation which is known as an inhibition of key inflammatory signaling networks [28]. Sari et al reported that familial Mediterranean fever mutations were detected highly in resistant pediatric UC cases and colchicine therapy may be beneficial in these patients [11].…”
Section: Discussionmentioning
confidence: 99%